Do the work! : an antiracist activity book - Bell, W. Kamau; Schatz, Kate (Workman Publishing, 2022)
"Revelatory and thought-provoking, this highly illustrated, highly informative interactive workbook gives readers a unique, hands-on understanding of systemic racism--and how we can dismantle it. Packed with activities, games, illustrations, comics, and eye-opening conversation, Do the Work! Challenges readers to think critically and act effectively. Try the "Separate but Not Equal" crossword puzzle. Play "Bootstrapping, the Game" to understand the myth of meritocracy. Test your knowledge of racist laws by playing "Jim Crow or Jim Faux?" Have hard conversations with your people (scripts and talking points included). Be open to new ideas and diversify your "feed" with a scavenger hunt. Team up with an accountability partner and find hundreds of ideas, resources, and opportunities to DO THE WORK!"--